2007
DOI: 10.1016/j.jaci.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to mouse allergen and asthma and asthma morbidity among women in Boston

Abstract: Recent studies have shown that mouse allergen is prevalent and potentially important in both urban and suburban environments, particularly in homes of subjects with asthma sensitized to this allergen. 1-4 However, little is known about the relation of sensitization to mouse allergen to asthma morbidity in adults with asthma outside the occupational laboratory setting. In this study, we evaluated whether sensitization to mouse allergen is a cause of morbidity in women with asthma from a range of socioeconomic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…19, 20 Home exposure to mouse allergen in the inner-city has been associated with increased asthma morbidity. 21 Recent data suggest that mouse allergen, more so than cockroach allergen, may be the most relevant urban allergen exposure. 22 Ahluwalia et al observed that in an inner-city community with high exposure to mouse and cockroach allergens, mouse allergen was more strongly and consistently associated with poor asthma outcomes.…”
Section: Allergic Rhinitis and Environmental Allergen Exposurementioning
confidence: 99%
“…19, 20 Home exposure to mouse allergen in the inner-city has been associated with increased asthma morbidity. 21 Recent data suggest that mouse allergen, more so than cockroach allergen, may be the most relevant urban allergen exposure. 22 Ahluwalia et al observed that in an inner-city community with high exposure to mouse and cockroach allergens, mouse allergen was more strongly and consistently associated with poor asthma outcomes.…”
Section: Allergic Rhinitis and Environmental Allergen Exposurementioning
confidence: 99%
“…26 In addition, the presence of dust mite, cat, cockroach, and mouse allergen in the home have been found to be related to airway hyperresponsivesness 30 and sensitization to dust mite and cat allergen are related to wheezing. 31 Mouse allergen's contribution to asthma has also been studied, 9,[32][33][34][35] and significantly more asthmatic children have been shown to be allergic to mice (assessed by skin prick) when mouse allergen levels reach a certain cutpoint. 36 In all, increased exposure to allergens, particularly dust mites and cockroaches, is related to an increased risk for the development of asthma.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
“…The results confirmed that the introduction of the selected mutations did not affect the efficiency of antigen processing and presentation. Although several mouse antigens have been identified, including serum proteins, dander components and other urinary proteins [65], Mus m 1 is the most important allergen component in epidemiological terms [66]. Thus, in the perspective of designing patient-tailored immunotherapy, Mus m 1 will represent by far the most relevant component to be included in vaccines for mouse-allergic individuals.…”
Section: Discussionmentioning
confidence: 99%